RESOLUSI KONFLIK KEPERCAYAAN DALAM TOLERANSI BERAGAMA PADA MASYARAKAT MULTIKULTURAL DI INDONESIA - Andi Muhammad Arief Malleleang; I Gede Sumertha KY; Puguh Santoso; Herlina Juni Risma Saragih (Institut Pendidikan Tapanuli Selatan, 2022)
Being a multicultural society is a challenge for Indonesia. The diversity of cultures and beliefs is increasingly causing conflict in the community. Conflicts of thought are often a problem, especially religious conflicts. Indonesia is a pluralistic country with diverse ethnicities, races, cultures, languages, and religions. Indonesia knows several religions, namely Islam, Roman Catholicism, Protestantism, Hinduism, Buddhism, and Confucianism. These religions have different principles and beliefs. The lack of a social order to properly manage these differences has the potential to create conflict. It is a common understanding that inter-religious conflicts are contrary to religious principles, which teach the values ​​of peace. Handling social conflicts like this must be based on teaching the importance ​​of tolerance between religious communities in a multicultural society. Conflict resolution of beliefs in tolerance of diversity can be achieved by internalizing education, preventing identity politics in a democracy, and inclusive leaders in knitting multicultural values ​​in Indonesia. This study uses a qualitative approach with data and literature sources related to resolving conflicts of trust in a multicultural society in Indonesia.